Pengaruh penambahan air rebusan pindang terhadap sifat fisikokimia dan sensori produk nori-like dari Ulva lactuca : The effects of addition of salted boiled fish wastewater on the physicochemical and sensory profile of nori-like product from Ulva lactuca - Alaf, Afifah Hanaa Nur; Santoso, Joko; Ramadhan, Wahyu (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2024)
Ulva lactuca seaweed can be used to produce Nori-like goods using salty boiling fish effluent. The objective of this study was to assess the chemical, sensory, and color features of a specific nori-like formula derived from U. lactuca with the inclusion of cooked fish water concentrate. The manufacturing of nori-like goods involves the addition of varying quantities of boiled water concentrate at different stages of the process, specifically at 0%, 1%, 2%, 3%, and 4% concentrations. This research involved the analysis of sensory test results, proximate and dietary fiber content, amino acids, water activity, and color. The nori-like mixture was prepared by adding 3% concentrated heated water. The nori-like items produced in this study exhibited diminished nutritional value compared to commercially available nori. Significantly, the findings indicate that incorporating an extra 3% boiled water concentrate during the manufacturing of nori-like can enhance its nutritious content in comparison to the control nori-like (which does not contain boiled water concentrate). The formula selected yielded the following results: 12.77% water content, 14.53% ash, 17.02% protein, 5.88% fat, and 25.77% dietary fiber. The primary amino acids present in the selected nori-like samples were histidine, glutamic acid, and glycine. The aw value of the product was 0.59, while the L, a, and b values were 14.28, 0.76, and 14.44, respectively.